Dawkins is Dead: Long Live Evolution! - Cunningham, Conor (New blackfriars, 2015)
What the late Stephen J Gould baptized ultra-Darwinism is anti-evolutionary. In so being, it leads to the undermining of science, rationality, and, lastly, to ethical nihilism, wherein any notion of humanism is impossible, and this for one simple reason – there is now no such thing as a human. In addition, we argue that ultra-Darwinism is a progeny of crass philosophical dualism, and this leads it to despise matter and the material world, even though, paradoxically, it espouses materialism. We conclude that the theory of evolution invalidates ultra-Darwinism.